Forming of Students Valeological Culture in Studying of Natural-Science Disciplines (by Example of Physics Course) - E. V. Ermakova; L. V. Gubanova; O. N. Berdyugina; G. S. Koshcheyeva (Научный диалог, 2017)
The article is devoted to the problem of valeological culture education in the process of studying of natural-science disciplines at school. The importance of developing skills aimed at the development of a healthy lifestyle in the process of realization of intersubject links on the example of studying of a school course of physics is noted. It is shown that in explaining to students the physical laws of nature, phenomena and processes the most appropriate is the use of specific examples, including the area of valeology, which not only broaden pupils’ outlook, but also affect the development of their culture of health. The article focuses on pedagogical techniques, allowing the teacher to develop individual abilities of students and create an atmosphere of success for each student both in the classroom and in extracurricular time in self-preparation for classes. Different forms of work are described that students can fulfill implementing interdisciplinary links between valeology and physics: self-dependent development of physics tasks using valeology material, writing essays, making presentations, preparing reports, making visual teaching aids, etc. It is concluded that this work allows the learner not only to accumulate knowledge about health care, but also to apply them in practice.